Genotype–phenotype correlations in 18 European patients with heterozygous KIF1A variants: key considerations for assessing KIF1A variant causality - Uhrova Meszarosova, Anna; Galiart, Elea; Lassuthova, Petra; Kolokotronis, Konstantinos; Seidl, Benjamin; Musilova, Alena; Peckova, Anna; Takacsova, Alena; Vyhnalkova, Emilie; Grecmalova, Dagmar; Vlckova, Eva; Skutilova, Vladana; et al. (Frontiers in Medicine, 2026)
BackgroundVariants in the KIF1A have been associated with a wide range of phenotypes. Most variants are found in the protein’s motor domain. The clinical phenotype of KIF1A-associated disorders (KAND) correlates with the position and the type of variant. Missense variants in the motor domain are predominantly associated with severe phenotypes and often occur de novo.MethodsPatients from the Czech Republic and Switzerland were identified during DNA diagnostics for neuromuscular or neurodevelopmental disorders. Clinical and genetic data were analyzed retrospectively.ResultsA total of 18 patients with heterozygous KIF1A variants were reported. The clinical spectrum ranges from a very severe congenital phenotype to mild spastic paraplegia or early-onset slowly progressive neuropathy. Among patients with early clinical manifestation (n = 13; congenital symptoms, gross motor delay, complicated/pure spastic paraplegia, neuropathy), all detected variants were missense and localized in the motor domain, eight times confirmed to be de novo. In individuals with adult onset (n = 5; all spastic paraplegia), a frameshift variant outside the motor domain was also detected in one case.ConclusionKAND phenotypes are not only limited to severe and early-onset phenotypes but also include adult-onset less severe ones. The localization of a missense KIF1A variant in the motor domain corresponds with a more severe disease, but not exclusively. Given the broad phenotypic spectrum associated with KIF1A variants, each variant should be individually evaluated for pathogenicity. Based on our findings, we propose a supporting algorithm outlining key considerations to support variant causality and the prediction of the associated phenotype.